Larval gut microbiome of Pelidnota luridipes (Coleoptera: Scarabaeidae): high bacterial diversity, different metabolic profiles on gut chambers and species with probiotic potential - Falqueto, Silvia Altoé; de Sousa, Janaína Rosa; da Silva, Rafael Correia [UNESP]; da Silva, Gilvan Ferreira; Pinheiro, Daniel Guariz [UNESP]; Soares, Marcos Antônio (My University, 2022)
Pelidnota luridipes Blanchard (1850) is a tropical beetle of the family Scarabaeidae, whose larvae live on wood without parental care. Microbiota of mid- and hindgut of larvae was evaluated by culture-dependent and independent methods, and the results show a diverse microbiota, with most species of bacteria and fungi shared between midgut and hindgut. We isolated 272 bacterial and 29 yeast isolates, identified in 57 and 7 species, respectively, while using metabarcoding, we accessed 1,481 and 267 OTUs of bacteria and fungi, respectively. The composition and abundance of bacteria and fungi differed between mid- and hindgut, with a tendency for higher richness and diversity of yeasts in the midgut, and bacteria on the hindgut. Some taxa are abundant in the intestine of P. luridipes larvae, such as Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria; as well as Saccharomycetales and Trichosporonales yeasts. Mid- and hindgut metabolic profiles differ (e.g. biosynthesis of amino acids, cofactors, and lipopolysaccharides) with higher functional diversity in the hindgut. Isolates have different functional traits such as secretion of hydrolytic enzymes and antibiosis against pathogens. Apiotrichum siamense L29A and Bacillus sp. BL17B protected larvae of the moth Galleria mellonella, against infection by the pathogens Listeria monocytogenes ATCC19111 and Pseudomonas aeruginosa ATCC 9027. This is the first work with the larval microbiome of a Rutelini beetle, demonstrating its diversity and potential in prospecting microbial products as probiotics. The functional role of microbiota for the nutrition and adaptability of P. luridipes larvae needs to be evaluated in the future.
Keywords: Grub; Lytic enzymes; Metabarcoding; Probiotics; Rutelinae; Saproxylic beetles